Lumberjanes. 3, A terrible plan - Stevenson, Noelle; Watters, Shannon (Stevenson, Noelle. Comic books., 2016)
During a quiet day at camp, Mal and Molly stumble upon the Bear Woman who whisks them into a prehistoric adventure. Meanwhile back at camp, Jo, April, and Ripley try to earn every badge possible.